Skin signs of selenium poisoning. - Chaparro-Reyes, D.; Valderrama, J.; Prada-Gwiner, N.; Vivas-Restrepo, L.; Espitia-Hernandez, D. (European Journal of Pediatric Dermatology, 2023)
Selenium poisoning is a rare event and even more rare is the one that follows the ingestion of Lecythis ollaria seeds; therefore, in the literature there are few cases reported in humans, never under the age of 18 in Colombia. The actual report presents the case of a pediatric patient who developed acute selenium poisoning after ingesting a significant number of these seeds. The clinical presentation was characterized by vomiting, diarrhea, jaundice, hematuria, diffuse alopecia, and gray nail pigmentation.